Plan estratégico de gestión administrativa y comercial para el fortalecimiento de la competitividad de la empresa Kaypitex de Otavalo - Arias, Jéssica A. (2018)
This work was carried out due to the company's KaypiTex, in recent years has lost competitiveness, for this reason we designed a strategic plan of commercial and administrative management for strengthening the competitiveness of the company KaypiTex, with the objective of increasing the level of sales, productivity and diversify the market, promoting the textile offer that the company owns. This document describes the methodology used for the development of the strategic plan, began with an analysis of the background and trends of strategic plans for institutional development and commercial enterprises in tissues, which made it possible to determine the basis for the implementation and design of the strategic plan.